Um aplicativo de segurança compartilhado denominado: ESCOLTAPP - Barros, Edilson Melo de (2019)
Insecurity is a public problem and is commonly present in the daily lives of the population. It is notorious that many people seek alternatives to minimize or avoid situations that cause risks to them or their loved ones. Technology is shown as an efficient tool in this scenario, since it assists in various situations and quickly and practically. The present work aims at allying the technology with the problem of the lack of insecurity, through the creation of a mobile application with the purpose of providing the end user with a proposal for help in adverse situations. The app can be used by anyone with a phone with Android or IOS settings. The ultimate goal of the application is to provide the client with a useful alternative so that they can mitigate the problems of personal insecurity upon return to their home, as long as their family members have protection or contracted services such as private or street safety. For the implementation of the project, tests are in progress so that all the particularities are tested, before the feasibility and final disclosure of the application.